Impact of polygeNic risk score for glaucoma on psycHosocial ouTcomes (INSiGHT) study protocol. - Giorgina Maxwell; Robert Allen; Simone Kelley; Lucinda Hodge; Georgina L Hollitt; Mathias Seviiri; Daniel Thomson; Joshua Schmidt; Jamie E Craig; Sarah Cohen-Woods; Emmanuelle Souzeau (PLoS ONE)
Glaucoma is the leading cause of irreversible blindness with early detection and intervention critical to slowing disease progression. However, half of those affected are undiagnosed. This is largely due to the early stages of disease being asymptomatic; current population-based screening measures being unsupported; and a lack of current efficient prediction models. Research investigating polygenic risk scores (PRS) for glaucoma have shown predictive ability to identify individuals at higher risk. Potential clinical applications include identification of high-risk individuals, resulting in earlier diagnosis and treatment to prevent glaucoma blindness, and adjusted monitoring for low-risk individuals. However, the psychological impact of receiving glaucoma PRS is unknown. There is a critical need to evaluate risk information communication and assess the impact of receiving results, to support clinical implementation of glaucoma PRS testing. In this prospective study, 300 individuals from the GRADE (Genetic Risk Assessment of Degenerative Eye disease) study will be recruited to investigate the psychosocial impact of disclosing polygenic risk results for glaucoma. GRADE aimed to apply PRS testing on 1,000 unexamined individuals aged 50 years or older from the general population and examine a subset of these individuals to assess the clinical validity of PRS to detect glaucoma. In this study, individuals each from the bottom decile (10%), top decile (10%), and middle (45-55%) of the PRS distributions will be invited to receive research glaucoma PRS results. Participants who choose to receive their results will complete up to four questionnaires (prior to receiving their results, and subsequently two-weeks, six- and 12-months after receiving their result). The questionnaires will include health belief model measures and assess glaucoma anxiety, general anxiety and depression, test-related distress, decisional regret, and recall and understanding of results. This research will provide guidance for the implementation of polygenic risk testing into clinical practice and inform delivery strategies.